Families bereaved by road traffic crashes: linkage of mortality records with 1971–2001 censuses. Issue 6 (3rd December 2009) - Sullivan, R; Edwards, P; Sloggett, A; Marshall, C E
Abstract : Objective: To estimate the number of people alive in England & Wales who have lost a close family member in a fatal road traffic crash. Design: Linkage of mortality records in a sample of 1.1% of the population during 1971–2005 with records from the 1971, 1981, 1991 and 2001 censuses. For each person killed in a road traffic crash, the number of close family members still alive in 2005 was estimated by applying life table probabilities of survival. Setting: England & Wales, UK. Subjects: Adults and children killed in road traffic crashes 1971–2005. Main outcome measure: Number of close family members alive in 2005. Results: In a sample of approximately 1.1% of the population in 1971–2005, a total of 1801 adults and children died in road traffic crashes. These deaths left 6467 close family members bereaved in 2005, corresponding to a total of 590 518 bereaved in the population (including 131 399 parents who had lost a child and 107 384 offspring who had lost a parent). Conclusion: Over 1% of the population of England & Wales alive in 2005 had lost a close family member in a fatal road traffic crash since 1971. This may imply a greater public health burden of road traffic crashes than previously estimated.